Necrotizing enterocolitis leads to disruption of tight junctions and increase in gut permeability in a mouse model - Srikanth Ravisankar; Rodney Tatum; Parvesh M. Garg; Maja Herco; Prem S. Shekhawat; Yan-Hua Chen (BMC Pediatrics, 2018)
Abstract Background Necrotizing enterocolitis (NEC) is a leading cause of death in preterm infants. Neonates weighing <1500 grams are at the highest risk for acquiring NEC, with a prevalence of nearly 7-10%, mortality up to 30%, and several long-term complications among survivors. Despite advancements in neonatal medicine, this disease remains a challenge to treat. The aim of this study is to investigate the effect of NEC on gut epithelial tight junctions and its barrier function using a NEC mouse model. Methods Three-day old C57BL/6 mouse pups were fed with Esbilac formula every 3 hours and then subjected to hypoxia twice daily followed by cold stress. Dam fed pups from the same litters served as controls. Pups were observed and sacrificed 96 hours after the treatments and intestines were removed for experiments. The successful induction of NEC was confirmed by histopathology. Changes in tight junction proteins in NEC intestines were studied by western blotting and immunofluorescent microscopy using specific protein markers. The gut leakage in NEC was visualized using biotin tracer molecules. Results Our study results demonstrate that we induced NEC in >50% of experimental pups, pups lost nearly 40% of weight and their intestines showed gross changes and microscopic changes associated with NEC. There were inflammatory changes with loss of tight junction barrier function and disruption of tight junction claudin proteins in the intestines of NEC mouse model. We have demonstrated for the first time that NEC intestines develop increased leakiness as visualized by biotin tracer leakage. Conclusions NEC leads to breakdown of epithelial barrier due to changes in tight junction proteins with increased leakiness which may explain the transmigration of microbes and microbial products from the gut lumen into the blood stream leading to sepsis like signs clinically witnessed.